Evaluasi Kinerja Sistem Penyediaan Air Minum (SPAM) PT. Adhya Tirta Batam 2005 - 2014 Kepulauan Riau - Herdiansyah Herdiansyah; Ari Sandhyavitri; Andy Hendri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
PT. Adhya Tirta Batam is the first drinking water company in Indonesia accepted a concession contract to manage and distribution of water in Batam Island at 1995-2020 and now ATB was be the best of drinking water company in Indonesia with many achievement. ATB was improve the customers service since 1995 only has 13.710 customers with 30% coverage areas and then in 2014 ATB has 227.054 customers with 99,5% coverage areas. In order ATB can give a good services, ATB need the evaluation in some performance indicators (operational, service, and human resources) from 2005 until 2014.Based on evaluated results in performance indicators ATB in 2005-2014, ATB has a good trend in every years and customers of ATB has a high satisfaction in services of ATB. ATB achievemented during 1995-2014 was confirm that Public Private Partnership (PPP) in water sector can give the good services especially from coverage areas expansion and can operated with efficient.Keywords : PT. Adhya Tirta Batam, Concession Contract, Drinking Water Company,Public Private Partnership, Customers Satisfaction.